(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
This research endeavors to assess the role of the Lemar TV channel in portraying Pashtun cultural values through an in-depth examination of the "Lemar Makham" program. The study, conducted over six months, employed qualitative research methodologies, explicitly adopting the case study and content analysis approaches. A comprehensive analysis of 24 episodes, each comprising 6 segments, was undertaken to explore six distinct cultural elements: clothing, food, music, poetry and literature, language, and cultural innovation. The research findings signify the program’s success in effectively reflecting Pashtun culture across multiple dimensions. Literature and poetry emerge as the predominant cultural element, constituting 100 percent of the sample size. Subsequently, language is represented at 91 percent, music at 75 percent, clothing at 55 percent, food at 50 percent, and cultural innovation at the lowest percentage, amounting to 15 percent within the entire sample size. In conclusion, this research affirms that the "Lemar Makham" program serves as a compelling and accurate portrayal of Pashtun culture and literature in Afghanistan. The nuanced exploration of various cultural elements within the program contributes to its effectiveness in representing and preserving the rich cultural heritage of the Pashtun community.